2017
DOI: 10.7554/elife.28118
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the melanocortin-4 receptor in mice causes dilated cardiomyopathy

Abstract: Haploinsufficiency of the melanocortin-4 receptor, the most common monogenetic obesity syndrome in humans, is associated with a reduction in autonomic tone, bradycardia, and incidence of obesity-associated hypertension. Thus, it has been assumed that melanocortin obesity syndrome may be protective with respect to obesity-associated cardiovascular disease. We show here that absence of the melanocortin-4 receptor (MC4R) in mice causes dilated cardiomyopathy, characterized by reduced contractility and increased l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…To further understand how Mc4r signaling regulates limb regeneration, we investigated the production of reactive oxygen species (ROS) during tadpole limb regeneration. Elevated ROS levels in the hypothalamus have been implicated in regulating energy metabolism (Diano, 2013; Drougard et al, 2015) and a recent study showed that Mc4r regulates ROS production in mouse cardiomyocytes (Litt et al, 2017). Earlier work in Xenopus also showed that ROS is important for tail regeneration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further understand how Mc4r signaling regulates limb regeneration, we investigated the production of reactive oxygen species (ROS) during tadpole limb regeneration. Elevated ROS levels in the hypothalamus have been implicated in regulating energy metabolism (Diano, 2013; Drougard et al, 2015) and a recent study showed that Mc4r regulates ROS production in mouse cardiomyocytes (Litt et al, 2017). Earlier work in Xenopus also showed that ROS is important for tail regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…ROS are canonical mediators of tissue damage and have both positive and negative effects on wound healing and organ regeneration. A recent study revealed that an Mc4r mutation causes dilated cardiomyopathy, with ultrastructural changes in mitochondrial morphology and increased reactive oxygen species (ROS) production (Litt et al, 2017). In our study we found that reduced expression of Mc4r in the limb cells led to decreased ROS production (Figure 7), which is contradictory to the increased level of ROS found in the Mc4r mutant myocardial tissues (Litt et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MC4R activation results in decreased food intake and increased energy expenditure, hence decreased body weight [ 27 ]. In the cardiovascular system, MC4R activation increases heart rate and blood pressure, whereas MC4R deficiency causes dilated cardiomyopathy in mice [ 28 ]. MC4R also promotes glucose homeostasis, independent of its action on the body weight, providing additional therapeutic benefit (reviewed in [ 25 ]).…”
Section: The Melanocortin-4 Receptormentioning
confidence: 99%
“…For example, Liu and colleagues observed that MC4R activation using the agonist RO27-3225 significantly protected against brain injury, including reduced brain edema, blood-brain barrier permeability, and inflammation of cerebral tissues, evoked by intra-abdominal hypertension and hemorrhagic shock [41]. Gava et al also showed improved cardiac function in a model of heart failure induced by permanent ligation of the left anterior descending coronary artery [42], whereas loss of MC4R function has been associated with dilated cardiomyopathy in mice [43]. These studies along with MC4R's role in appetite, body weight homeostasis, SNS activity, and BP reinforce the importance of understanding how the MC4R exerts its multiple actions and how these effects can be differentially activated by synthetic agonists.…”
Section: Future Directions In the Development Of Mc4r Agonistsmentioning
confidence: 99%